2019
DOI: 10.3390/ijerph16183452
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of NDVI in the Growing Season of the Tibetan Plateau During the Past 17 Years and Its Response to Climate Change

Abstract: The fragile alpine vegetation in the Tibetan Plateau (TP) is very sensitive to environmental changes, making TP one of the hotspots for studying the response of vegetation to climate change. Existing studies lack detailed description of the response of vegetation to different climatic factors using the method of multiple nested time series analysis and the method of grey correlation analysis. In this paper, based on the Normalized Difference Vegetation Index (NDVI) of TP in the growing season calculated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 62 publications
2
27
1
Order By: Relevance
“…The climate change trend showed that before 2014, the annual precipitation and annual mean temperature of the QTP both increased, and the regional climate was "warming and humid." However, after 2014, an extreme drought year, the annual precipitation in 2015 dropped rapidly, and this result has also been confirmed by relevant research [85]. Moreover, this study found that the annual precipitation on the QTP began to decline slowly from 2000 to 2018, while the annual mean temperature displayed an upward trend.…”
Section: Discussionsupporting
confidence: 81%
“…The climate change trend showed that before 2014, the annual precipitation and annual mean temperature of the QTP both increased, and the regional climate was "warming and humid." However, after 2014, an extreme drought year, the annual precipitation in 2015 dropped rapidly, and this result has also been confirmed by relevant research [85]. Moreover, this study found that the annual precipitation on the QTP began to decline slowly from 2000 to 2018, while the annual mean temperature displayed an upward trend.…”
Section: Discussionsupporting
confidence: 81%
“…Grey correlation analysis, which has been widely used in various fields, is an effective means of studying fuzzy systems [18][19][20]. When grey correlation analysis is carried out, transformation of the mean values is first performed to make the dimensions consistent.…”
Section: Results Of Analysis Of Grey Degree Of Associationmentioning
confidence: 99%
“…NDVI reflects regional vegetation health status and vigor. Quarterly NDVI and annual NDVI were acquired through the Maximum Value Composite (MVC) method [32]. The total column ozone data and environmental data at 14:00 from ERA5 were selected as potential influencing factors.…”
Section: Data and Data Preprocessingmentioning
confidence: 99%